Analysis of risk factors for acute pancreatitis complicated with pancreatic sinistral portal hypertension and construction of predictive model - Zhao, Xin; Mao, Tian-Yang; Jiang, Kang-Yi; Xie, Qing-Yun; Yang, Jie; Du, Bo; Wang, Zhi-Xu; Fu, Jin-Qiang; Gao, Feng-Wei; Lei, Ze-Hua (Frontiers in Physiology, 2024)
Objective:This study aimed to identify the risk factors for AP concurrent with PSPH and use these factors to build a related predictive model. Materials and methods: We collected clinical data from 282 patients with AP. 192 patients were used as a training group and 90 patients as a validation group. Univariate and multivariate analyses were used to identify independent risk factors for AP complicated with PSPH, and then a nomogram was established. The models are cross verification and Internal verification. The predictive ability and accuracy of the model were evaluated based on the working curve of the subjects and the calibration curve, respectively. The clinical value of the model was evaluated using decision curve analysis (DCA). Results: The univariate analysis revealed significant differences in the occurrence of PSPH with respect to sex, recurrent AP, history of hypertension, smoking history, patency of the splenic vein, pancreatic necrosis or pancreatic pseudocyst formation, the most significant site of pancreatic swelling, presence of a Dmure D polymer, MCTSI, and involvement of lipase and amylase. The logistic multivariate regression analysis showed that male sex, splenic-vein stenosis or occlusion and swelling were located in the body-tail, and MCTSI was an independent risk factor for PSPH. The nomogram and ROC curve were constructed. The area under the working curve of the subjects was 0.91, and the sensitivity and specificity were 82.5% and 89.1%, respectively. In the validation group, the C-index is 0.826. The nomogram was internally validated using 1000 bootstrap samples, and the c-index was 0.898. The calibration curve demonstrated that the predicted probability was concordant with the observed probability, and the DCA confirmed that the model had robust clinical utility. Conclusion: Male sex, splenic-vein stenosis or occlusion, recurrent AP, and swelling are located in the body-tail, and MCTSI is an independent risk factor for the occurrence of PSPH. The predictive model developed for AP complicated with PSPH may serve toward developing preventive and therapeutic approaches for PSPH.